Human Resources Management in the Company, Performance and Sense of Commitment - Santos, Armando Cuesta (Review of Business Management, 2015)
Objective – The objective was to measure and to evaluate the construct “sense of commitment”, to insert it in the activities of Human Resources Management (HRM). Design/methodology/approach – The used methods were interviews, mathematic modeling, and statistical correlation. Findings – As the results, mathematical models were obtained and used to process the application of instruments with theoretical support related to the studied construct, as well as its validation for the socio-cultural particulars of Cuban companies’ employees, along with its conceptual insertion in the activities of HRM for its planning and strategic management control. Practical implications – Insertion of the “sense of commitment” in the HRM activities of the company, considering its planning and strategic management control. Contributions – The measurement of the “sense of commitment”, technically inserting it in the planning and control of the HRM activities in the company.